How Islamic Scholarship Birthed Modern Astronomy - Haque, Anwar Ul (International Journal of Pathology, 2021)
“There were so many contributions over a millennium that it’s impossible to pick just a few.” By Shannon Stirone | Published: Tuesday, February 14, 2017 WikiMedia Commons Following is an excellent article we took fromhttps://astronomy.com/news/2017/02/muslim-contributions-to-astronomy (We thank Astronomy for this very informative article (Editor) Astronomy may be the oldest natural science in the world. Before humans ever took to systematically studying the skies, we were craning our necks upwards, observing the curious movements of some bright points of light, and the stillness of others. Civilizations around the world have incorporated astronomical observations into everything from their architecture to their storytelling and while the pinnacle of the science is most commonly thought to have been during the Renaissance, it actually began a thousand years earlier and 5,000 miles to the East. Around the 6th century AD, Europe entered what’s known as the Dark Ages. This period of time from around 500 AD until to the 13th century witnessed the suppression of intellectual thought and scholarship around the continent because it was seen as a conflict to the religious views of the church. During this time the written word became scarce, and research and observations went dormant.